A Systematic Literature Review on Conditional Cash Transfers in Organisation of Islamic Cooperation Countries for Tackling Poverty - Mohamed Esa, Mohd Suffian; Yaacob, Salmy Edawati; Wahid, Hairunnizam (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
Conditional Cash Transfer (CCT) programs have been highly effective in reducing poverty globally, particularly in countries such as Brazil and Mexico. However, numerous OIC countries continue to experience high poverty levels, emphasizing the need for programs that are specifically adapted to their unique socio-economic contexts. The goal of this study is to systematically review and synthesize the evidence on the effectiveness of Conditional Cash Transfer (CCT) programs in poverty eradication in OIC member countries. This study utilized a systematic review following the ROSES protocol for transparency and rigor. Inductive thematic analysis was applied to identify key patterns, synthesizing 23 articles published between 2018 and 2023 for comprehensive insights into the research topic. Five significant themes were identified based on the thematic analysis: (1) Health Conditionality and Impact on CCT Programs; (2) Education Conditionality and Impact on CCT Programs; (3 CCT Programs Impact on Poverty; (4) Issues and Challenges in CCT Programs; (5) Intervention in CCT Programs. Thirteen sub-themes were built from these five fundamental concepts. This study reviews recent advancements in CCT programs and their impact on poverty alleviation in OIC countries, offering insights for implementation and providing valuable information for scholars. It emphasizes the potential integration of Islamic fiscal resources, such as zakat, and the incorporation of religious principles as conditionalities within CCT models from an Islamic legal perspective. These aspects offer promising avenues for future research, providing valuable insights that could enhance poverty reduction strategies and serve as important guidance for scholars and policymakers.